Analisis Kualitas Layanan Perpustakaan Kampus B Universitas Airlangga Melalui Integrasi Importance Performance Analysis (IPA), Dan Model Kano Serta Usulan Perbaikannya Menggunakan Cause And Effect Diagram - Fatorahman Fatorahman; Yetty Dwi Lestari (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2015)
The aims of this study to identify the attributes of existing service quality on B Campus Library of Airlangga University as well as determine the level of priority level of each need by integrating models and Kano methods, Importance Performance Analysis, furthermore, it also identyifying the root causes of the three attributes of service quality on B Campus Library of Airlangga University were entered into the forth kuadrant by using Cause and Effect Diagram, and give recommendation for improvement based on problems identification by Cause and Effect Diagram. The approach used in this research  is a qualitative approach with the kind of descriptive research. Data used are primary and secondary data. Analysisi data used descriptive analysis with the help of IBM SPSS Statistics 20 and Microsoft Office Excel.This research used 23 atributes of service quality. The result of the classification of data qith kano’s mode; stated that 22 atributes   of service quality. The results of the classification of data with Kano's model stated that 22 atributes are included into attractive category. Because none of attributes were included into the indifferent category, all of the attributes can be used in the integration of Kano's model and IPA methods. From the integration, comes three attributes of service quality that included into concentrate here area; the availbility of fast connection wifi and internet facilities, friendly, polite, orderly, and neat in officer services, and the availability of clean toilet facilities.The root of the problem cause the lack of quality in three attributes identified by Cause and Effect Diagram based on interviews with the B Campus Library of Airlangga University and also based on the author's observation results. Based on the identification of the three atributes with the quality of service, proposed recommendation to fix problem on each attributes. The recommendation includes several root of the problem, such as man, methods, equipment, and environment